Pengaruh Rasio Likuiditas, Leverage, dan Profitabilitas terhadap Dividen Pay Out Ratio (Studi pada Perusahaan Go-public di Bursa Efek Jakarta) - Anjar Wibisono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The research mainly aims at: (1) analyzing partially the effect of liquidity ratio, leverage, and profitability variables on dividend payout ratio of the company; and (2) analyzing simultaneously the effect of liquidity ratio, leverage, and profitability variables on dividend payout ratio of the company. Research type subsumes into quantitative descriptive using the population of manufacturing companies listed at the Corner of Jakarta Stock Exchange. Purposive sampling becomes a sample determination technique such that research sample includes 40 companies. Analysis tool used relates to Multiple Regression. F-test and t-test examine the significance using SPSS. Results of statistic analysis indicate that: simultaneously, independent variable has obvious effect on dependent variable. This becomes evident because F-count > Ftable. F-count reaches 47.314 and F-table equals to 2.25. Meanwhile, partial test or t-test shows that current ratio has negative effect on dividend payout ratio. Return on investment and return on equity have positive effect on dividend payout ratio meaning that if ROI and ROE improve, then dividend payout ratio also increase. The contribution of research will be giving the further description and the understanding of factors affecting the payment rate of dividend payout ratio because it seems being important guide for the company’s investor and manager in making decision through financial performance in consideration of liquidity ratio, leverage and profitability.Keywords: liquidity, leverage, profitability, dividend payout ratio